EFFECT OF INM ON NUTRIENTS UPTAKE AND YIELD OF MAIZEWHEAT CROPPING SEQUENCE AND CHANGES IN NUTRIENT AVAILABILITY IN TYPIC HAPLUSTEPTS - PRIYANKA; S. K. SHARMA; AJEET SINGH; J. K. SHARMA (The Bioscan, 2019)
Integrated nutrient management (INM) is an important tool to sustain of nutrients availability plants and improve soil fertility without any risk to environment. Field experiments were carried out during 2014-15 and 2015-16 under the ongoing AICRP on LTFE with Maize-Wheat cropping in Typic Haplustepts that initiated during kharif 1997 at the Instructional Farm of Rajasthan College of Agriculture, Udaipur. The experiment consisted of 12 treatment combinations viz., T1- Control, T2- 100%N, T3- 100%NP, T4- 100%NPK, T5- 100%NPK + Zn, T6- 100%NPK + S, T7- 100%NPK + Zn + S, T8- 100% NPK + Azotobacter, T9- 100% NPK + FYM 10 t ha-1, T10- FYM 10 t ha-1 + 100%NPK (-NPK of FYM), T11- 150%NPK and T12- FYM @ 20 t ha-1 with four replications in a RBD. Results showed that the nutrients availability in soil, nutrient uptake, and yield of crops were significantly response to combined application of organic and inorganic. The highest maize grain yield 4033 and 4053 kg ha-1 and stover yield 5290 and 5320 kg ha-1 were recorded fewer than T9 during 2014-15 and 2015-16, respectively. Similarly, the highest wheat grain yield 4939 and 5107 kg ha-1 and straw yield 7217 and 7270 kg ha-1 was recorded under T9 during both years. Maximum uptake of macro and micro nutrients by maize and wheat crop was recorded under application of integrated use of fertilizers along with manure i.e. T9. Soil enrichment with T11 resulted in highest positive balance of nitrogen and phosphorus in soil However, negative potassium balance was observed under all treatments.